Combined Analysis of the Effects of Exposure to Blue Light in Ducks Reveals a Reduction in Cholesterol Accumulation Through Changes in Methionine Metabolism and the Intestinal Microbiota - Xia, Daiyang; Yang, Lin; Cui, Jiajie; Li, Yu; Jiang, Xianzhi; Meca, Giuseppe; Wang, Shunxiang; Feng, Yan; Zhao, Yujie; Qin, Jiangfan; Zhu, Yongwen; Ye, Hui; et al. (Frontiers in Nutrition, 2021)
Monochromatic light is widely used in industry, medical treatment, and animal husbandry. Green-blue light has been found to stimulate the proliferation of satellite cells and the results of studies on the effects of blue light on poultry vary widely. It would be worthwhile to study the effect of blue light on poultry growth and how exposure to blue light affects metabolism and the intestinal microbiota. In this study, we irradiated Cherry Valley ducks with 460 nm wavelength light (blue light) for three weeks to explore the effects of blue light in comparison to those of white light (combined wavelength light) on animal growth and development. Our results showed that, under exposure to blue light, the body weight and average daily feed intake of ducks were decreased, but the leg muscle and relative length of the intestine were increased. Exposure to blue light chiefly enhanced the anti-inflammatory and antioxidant capacities of the animal and decreased lipid levels in serum and liver. Metabolomic analysis revealed that blue light heightened cysteine and methionine metabolism, and increased serum taurine and primary bile acid levels, as well as up-regulating the metabolites L-carnitine and glutamine. Treatment with blue light significantly increased the beta diversity of intestinal microbiota and the relative abundances of bile acid hydrolase-producing bacteria, especially Alistipes. These changes promote the synthesis of secondary bile acids to further enhance lipid metabolism in the host, thereby reducing cholesterol accumulation in ducks. These results should help us better understand the effects of exposure to blue light on metabolite levels and the intestinal microbiota, and suggest that it may be possible to use colored light to control the development of livestock and poultry.